Equity in early modern legal scholarship - Maniscalco, Lorenzo (Legal history library, 2020)
"[This book] takes the reader through the vast amount of legal writings on equity that were published in continental Europe in early modern times. The book offers the first comprehensive overview of the development of the legal concept of equity through the sixteenth and seventeenth century. During this time, equity scholarship broke with its medieval past and entered a lively debate on the nature and function of the concept. Lorenzo Maniscalco links these developments to the early modern identification of equity with Aristotelian epieikeia, a conceptual shift that brought down the barrier that divided theological and legal writings on equity and led to its development as a tool for the interpretation and amendment of legal rules"--